1994
DOI: 10.1080/01652176.1994.9694426
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of folic acid and plasma levels of bioactive folates after folic acid administration to pigs

Abstract: SUMMARYAfter intravenous (1 mg/kg body weight), intramuscular (1 mg/kg body weight) and oral (1 and 50 mg/kg body weight) administration of folic acid (FA) to pigs, plasma levels of FA, tetrahydrofolic acid (THF), 5-methyltetrahydrofolic acid (5MF) were determined by using highperformance liquid chromatography. The pharmacokinetic profile of plasma FA after oral administration indicated an absorption rate-limited elimination, i.e., so called 'flip-flop' phenomenon. The bioavailability of FA was quite low after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
0
8
1
Order By: Relevance
“…From the results of the present study, the three sources of reduced folates increased plasma folate levels, while synthetic FA did not increase plasma folate levels after single and long-term multiple oral administrations. Our results contradict those of the report by Kokue et al (1994). They reported an increase in plasma THF and 5CH 3 -THF, and FA levels after oral FA administration at a dose of 50 mg kg -1 body weight.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…From the results of the present study, the three sources of reduced folates increased plasma folate levels, while synthetic FA did not increase plasma folate levels after single and long-term multiple oral administrations. Our results contradict those of the report by Kokue et al (1994). They reported an increase in plasma THF and 5CH 3 -THF, and FA levels after oral FA administration at a dose of 50 mg kg -1 body weight.…”
Section: Discussioncontrasting
confidence: 57%
“…They reported an increase in plasma THF and 5CH 3 -THF, and FA levels after oral FA administration at a dose of 50 mg kg -1 body weight. The difference with the present experiment may be age-related because young pigs were used by Kokue et al (1994). Indeed, it has been shown that intestinal mucosa may be more permeable in young pigs than in adults to oral administration of polar antibiotics (Nouws 1992).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…not increase after oral administration of PteGlu, even at a high dose (4). In contrast, it has been known that the plasma concentration of 5-CH3-H4PteGlu increases after oral administration of PteGlu to rats (5).…”
Section: Discussionmentioning
confidence: 94%
“…These findings from in vivo and in vitro experiments demonstrate that the DHFR activity for PteGlu in pigs was much less than that in rats. The low DHFR activity in pigs may be one of the causal factors of the fact that the plasma H4PteGlu and 5-CH3-H4PteGlu did not in crease after oral administration of PteGlu, even at high dose (4,13). The reduction of PteGlu to H2PteGlu in pigs may be regarded as the rate-limiting step for the re duction of PteGlu to H4PteGlu, because the Vmax of pig liver DHFR for PteGlu was remarkably small, compared with that for H2PteGlu ( Table 3).…”
Section: Resultsmentioning
confidence: 99%